(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2008)
A 33-year-old man was found dead inside the bathroom of his house. He was a known alcoholic and was separated from his wife. He had had his dinner about half an hour before his death along with his friend. The face and neck of the deceased was bluish in colour with food particles mixed with mucous sticking around his mouth and cheek. A contusion of size 4×2cm was present on the right side frontal eminence of forehead He had allegedly been asphyxiated by a food bolus. The case, though not rare, is an important entity to mention.